MANAJEMEN RISIKO DALAM PENGEMBANGAN PROGRAM PENDIDIKAN INOVATIF BERBASIS TEKNOLOGI DIGITAL DI SEKOLAH ISLAM SWASTA - M. Agus Kurniawan; Suci Hartati (Jurnal Dinamika Pendidikan Islam, 2025)
The development of innovative educational programs based on digital technology in Islamic private schools presents significant learning transformation opportunities, but also poses various risks that need to be managed systematically. This research aims to identify, analyze, and formulate risk mitigation strategies in implementing digital technology-based educational programs in Islamic private school environments. Using a qualitative approach with case study methods at three private madrasah tsanawiyah in Lampung, namely MTs Hidayatul Mubtadiin Jati Agung, MTs Mathlaul Anwar Cintamulya, and MTs Darul Ma'arif Natar, this research collected data through in-depth interviews, direct observation, and document analysis. The results show that the main risks include aspects of technological infrastructure, educators' digital competence, integration of Islamic values, financial sustainability, and data security. Recommended mitigation strategies include developing an integrated risk management model, enhancing human resource capacity, curriculum adaptation, developing strategic partnerships, and strengthening technology governance. This research contributes to the development of a comprehensive risk management framework to support digital transformation in Islamic educational institutions while maintaining Islamic values that form the foundation of institutional identity.